Molecular and cytogenetic evidence of three sibling species of the Anopheles barbirostris Form A (Diptera:Culicidae) in Thailand - Saeung A. (2014)
Nine isoline colonies of Anopheles barbirostris Form A, derived from individual isofemale lines from Chiang Mai, Phetchaburi, and Kanchanaburi, were established in our insectary at Chiang Mai University. All isolines shared the same mitotic karyotype (X1, X2, Y1). Molecular analysis of deoxyribonucleic acid (DNA) sequences and polymerase chain reaction (PCR) products of ITS2, COI, and COII regions revealed three distinct groups: A1 (Chiang Mai), A2 (Phetchaburi), and A3 (Kanchanaburi). Crossing experiments among the three groups exhibited strong reproductive isolation, producing low and/or non-hatched eggs, and inviable and/or abnormal development of the reproductive system of F1-progenies. Asynaptic regions along the five polytene chromosome arms of F1-hybrid larvae clearly supported the existence of three sibling species within A. barbirostris Form A, provisionally named species A1, A2, and A3. © 2007 Springer-Verlag.